Faktor-faktor yang berhubungan dengan kejadian demam tifoid pada penduduk wilayah pinggiran sungai Musi di Seberang Ulu Palembang tahun 2019 (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Risk factors of typhoid fever in the residential population of Musi river 2019Purpose: This study aims to determine the factors related to the occurrence of typhoid fever in the residential of the Musi River in Seberang Ulu Palembang. Method: This research is a quantitative study using a case control design with a population of 106 samples using the Musi river suburb of Seberang Ulu using a proportional cluster sampling technique. Data analysis carried out in this study were univariate, bivariate, and multivariate.Results: The results of the study of the incidence of typhoid fever in the population of the Musi River region in Seberang Ulu showed a low socioeconomic (p value = 0.032), low education (p value = 0.015), individual hygiene (pvalue = 0,000), using the toilet (pvalue 0.025), clean water quality (p value = 0.034), garbage storage facility (pvalue = 0.006), fecal leasing facility (pvalue = 0.018) is related to the incidence of typhoid fever, age, gender, occupancy density is not relationship with the incidence of typhoid fever Based on the results of multivariate analysis, the variable waste disposal facility is the most influential variable with the Odds Ratio 3.557; 95% CI 0.951-13,229.Conclusion: It can be concluded that the waste disposal facilities in the Musi River suburb in Seberang Ulu are still not good and become a dominant factor influencing the incidence of typhoid fever so it is advisable to carry out outreach efforts to increase environmental awareness and provide garbage disposal infrastructure to meet the requirements of a healthy environment. and looking for trash transport officers to then be transported to temporary landfills.